Alum-based sludge (AbS) recycling for turbidity removal in drinking water treatment: an insight into statistical, technical, and health-related standpoints - Foroughi, Maryam; Chavoshi, Sona; Bagheri, Marziyeh; Yetilmezsoy, Kaan; Samadi, Mohammad Taghi (SPRINGER, 2018)
This study aimed to evaluate the feasibility of recycling alum-based sludge (AbS) generated from drinking water treatment facility for turbidity removal. A response surface methodology (RSM)-based modeling and factor analysis were first implemented for assessing the optimal conditions of four independent factors, such as initial turbidity concentration, humic acid (HA) concentration, pH, and AbS dose on the water turbidity removal via the use of AbS as a coagulant agent. The optimum values of the four main variables were determined as initial turbidity concentration=59.65 NTU, pH=5.56, AbS dose=19.71g/L, and HA concentration=12.28mg/L, and at the optimum conditions, the percentage of turbidity removal was obtained as 94.81 (+/- 1.01)% for real water. At the optimum conditions of AbS usage as a coagulant for real water samples, monitoring of water quality parameters of the process indicated no health-related concerns in terms of hardness (all types), alkalinity, pH, residual aluminum, and even bacteriological (fecal and total coliforms) contamination. The results indicated a potential for AbS recycling in the treatment plant as a coagulant agent, although some requirements should be fulfilled before full-scale application.
Keywords: Alum-based sludge; Box-Behnken experimental design; Response surface methodology; Turbidity removal; Water quality; RESPONSE-SURFACE METHODOLOGY; NATURAL ORGANIC-MATTER; WASTE-WATER; DESIRABILITY FUNCTION; AQUEOUS-SOLUTION; LOW-TEMPERATURE; OPTIMIZATION; ADSORPTION; COAGULANT; PERFORMANCE; Environmental Sciences & Ecology